Financial Pressure, Deferred Tax Expense, and Tax Aggressiveness: Audit Committee as the Moderation Variable - Suyanto, Suyanto; Alfiani, Hani; Apriliyana, Sari; Siciliya, Ayu Rida (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2021)
Purpose: This research aims to confirm the influence of financial pressure and deferred tax expense on tax aggressiveness and the moderation capability of audit committee.Method: The sample comprises manufacturing companies listed in the Indonesian Stock Exchange (BEI) throughout 2016-2019, which is filtered out to 102 sample data. This test was carried out using regression analysis and the interaction test of Moderated Regression Analysis (MRA).Finding: Firm size negatively influences tax aggressiveness, leverage positively influences tax aggressiveness, and deferred tax expense does not influence tax aggressiveness. Audit committee can moderate the positive influence of leverage on tax aggressiveness, but cannot moderate the influence of firm size and deferred tax expense on tax aggressiveness. These conclusions indicate that audit committee is unable to decrease tax aggressiveness.Novelty: This study considers the effectiveness of engaging audit committee as a factor that moderates the influence of financial pressure and deferred tax expense on tax aggressiveness in developing countries.